2019
DOI: 10.18203/2320-1770.ijrcog20191953
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent gynae clinic - need of the day: a prospective study at a tertiary care centre

Abstract: Background: To study common gynaecological problems in adolescent girls and to establish the need of adolescent clinic.Methods: A prospective study was conducted including 250 adolescent girls attending gynaecology OPD. Girls were evaluated by detailed history, thorough clinical examination and investigations such as haemogram, coagulation profile, hormonal assays, ultrasound examination of abdomen and pelvis, as and when indicated.Results: Majority of girls had complaints related to menstrual disorders i.e. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…We have done thalassemia screening of all the girls attended to our clinic only one patient having thalassemia trait. As shown in (Table 1) majority of girls fall in 15 to 19 years group, our patients age distribution is comparable with Jain et al, BMI of present study is comparable with Shanti et al 4,5 74 girls attained menarche before 10 years, are comparable to Shanti et al 5 Good nutrition and sedentary life style may be a reason for early menarche, further study may needed in large number. Girls presenting with various complaints are comparable with Goswami et al 6,7 As shown in (Table 5) menstrual problems are comparable with Nandita et al 8 As shown in (Table 6) menorrhagia group 24 girls required hospitalisation for correction of anaemia, 8 girls required 2 or more transfusions, 16 girls required 1 or more blood transfusion.…”
Section: Discussionsupporting
confidence: 89%
“…We have done thalassemia screening of all the girls attended to our clinic only one patient having thalassemia trait. As shown in (Table 1) majority of girls fall in 15 to 19 years group, our patients age distribution is comparable with Jain et al, BMI of present study is comparable with Shanti et al 4,5 74 girls attained menarche before 10 years, are comparable to Shanti et al 5 Good nutrition and sedentary life style may be a reason for early menarche, further study may needed in large number. Girls presenting with various complaints are comparable with Goswami et al 6,7 As shown in (Table 5) menstrual problems are comparable with Nandita et al 8 As shown in (Table 6) menorrhagia group 24 girls required hospitalisation for correction of anaemia, 8 girls required 2 or more transfusions, 16 girls required 1 or more blood transfusion.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, adolescent gynecological problems were seen to be more common in the late adolescent age-group of 16-18 years.In the present study, 53.3% of cases belonged to the age-group of 16-18 years. According to a study by Jain et al,4 95.5% of patients were from the late adolescent age-group (15-19 years) whereas in a study by Goswami et al, 5 56% of patients belonged to the agegroup between 17 and 19 years.…”
mentioning
confidence: 93%